2017
DOI: 10.2224/sbp.6704
|View full text |Cite
|
Sign up to set email alerts
|

How do servant leaders promote engagement? A bottom-up perspective of job crafting

Abstract: We drew on the literature addressing servant leadership and job crafting, self-determination theory, and the job demands–resources model, and hypothesized that employees who are supported by servant leadership would craft their own jobs to stay engaged and perform well. Chinese employees (N = 544) working in various organizations participated in a survey. We found that servant leadership, as evaluated by employees, predicted work engagement and that job crafting played a partial mediating role in this relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…Another important context factor that affects individual proactive behavior is leadership. Some empirical studies have found a positive role of employee-oriented leadership (Lichtenthaler & Fischbach, 2018), empowering leadership (Esteves & Lopes, 2017a;Kim & Beehr, 2018;Thun & Bakker, 2018) and servant leadership (Bavik, Bavik, & Tang, 2017;Harju, Schaufeli, & Hakanen, 2018;Yang, Ming, Ma, & Huo, 2017) in shaping employee approach crafting. Those leaders give autonomy to employees and encourage employees to pursue long-term goals, thereby promoting employees' motivation to craft.…”
Section: Antecedents Of Approach Craftingmentioning
confidence: 99%
“…Another important context factor that affects individual proactive behavior is leadership. Some empirical studies have found a positive role of employee-oriented leadership (Lichtenthaler & Fischbach, 2018), empowering leadership (Esteves & Lopes, 2017a;Kim & Beehr, 2018;Thun & Bakker, 2018) and servant leadership (Bavik, Bavik, & Tang, 2017;Harju, Schaufeli, & Hakanen, 2018;Yang, Ming, Ma, & Huo, 2017) in shaping employee approach crafting. Those leaders give autonomy to employees and encourage employees to pursue long-term goals, thereby promoting employees' motivation to craft.…”
Section: Antecedents Of Approach Craftingmentioning
confidence: 99%
“…Similarly, a study of servant leaders showed servant leaders directly influence employee work engagement but also indirectly foster work engagement by processes of job crafting (Yang, Ming, & Ma, 2017). A succinct definition of job crafting is changing the tasks, relationships, or cognitions related to work (Wrzesniewski & Dutton, 2001).…”
Section: Relational Leadership and The Jd–r Modelmentioning
confidence: 99%
“…Job crafting includes employee actions of reviewing their work identity and work meaning. Yang et al (2017) identified a process whereby servant leaders empower employees by allowing them to schedule tasks and solve their own work problems and also provide the “emotional healing” of employees by listening sensitively to their concerns. These actions of empowerment and emotional healing promote employee job crafting and subsequent work engagement.…”
Section: Relational Leadership and The Jd–r Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, transformational and servant leaders were found to overlap in the study's top 25 codes (i.e., commitment, service, and community) as shown in Table 5. Yang, Ming, Jianhong, and Huo () performed a study on servant leaders to find that the use of servant leadership increases employee engagement. Furthermore, servant leadership can help improve organizational culture.…”
Section: Discussionmentioning
confidence: 99%